Effect of high irradiation and cooling on power, energy and performance of a PVT system - Nasrin, Rehena; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (Elsevier, 2018)
Irradiation level is the key factor of photovoltaic power generation. Photovoltaic/thermal systems are more effective at concentrating power in areas of high irradiation as compared to traditional PV systems. High irradiation maintains the cell temperature and maximizes electrical-thermal energy. An optimum cooling system is required to remove the extra heat from a PVT system, leading to enhancement of overall performance. In this research, the effect of different high irradiation levels and cooling fluid flow rate are investigated in terms of cell temperature, outlet temperature, electrical-thermal energy and overall performance of PVT system. Finite element based software COMSOL Multiphysics has been used to solve the problem numerically in three-dimensional model. The numerical model has been validated with available experimental and numerical results. It is found that overall efficiency increases with increasing fluid flow rate and with an optimum cooling fluid flow rate of about 180 L/h. Electrical and thermal energy increase from 197 to 983 W and 1165–5387 W respectively, for increasing irradiation from 1000 to 5000 W/m2 with an optimized flow rate of 180 L/h. Electrical, thermal and overall efficiency are found to be about 10.6, 71 and 81.6% respectively, at the highest irradiation level of 5000 W/m2.